The 2014 Pengkalan Kubor by-election in the State of Kelantan, Malaysia: electoral democracy via opposition inter-party system - Ariff Aizuddin Azlan,; Zulkanain Abdul Rahman,; Amer Saifude Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Malaysian politics in the post-2008 has started to gain its own currency. People’s proclivity towards the rapid rise of the opposition was perceived as an emerging trend due to political instability. The direction is indeed escalating in a more persuasive ways. The advent of inter-party system establishment, particularly the opposition, has provided a significant political comprehension as it grew out of the misplaced ideological attachment. People started to opt for the opposition and perceived it as the bringer of dissenting voices and awaited yardstick to ensure greater participation and pave the way for democratization. The emerging trend in the post-2008 has to a certain extent disclosed an uneasy feeling for the ruling BN in maintaining some sort of penetrated status quo. However the case was a bit different in the September 2014 Pengkalan Kubor by-election. The by-election was called to be held and witnessed the struggling competing parties, namely between BN (UMNO) and PR (PAS). This article, somehow, found that the inter-party establishment (PR) strategy did not affect much in the case of Pengkalan Kubor byelection due to certain factors, be it internal and as well as external. Thus, it led to a strong suggestion that the opposition inter-party system establishment should (re)-strategize its collective strategy, making it more adaptable to the current socio-politico milieu.